(untitled) (Colombia Medica, 2022)
Background: Uruguay has the highest cancer incidence and mortality rates in Latin America. The National Cancer Registry of Uruguay, which has been in operation since 1992, provides epidemiological information on incidence and mortality at the country level. Objective: The objective of this article is to update the incidence and mortality figures by reporting the information for the period 2013-2017. Methods: All incident cases of invasive neoplasias except non-melanoma of the skin and all cancer deaths that occurred from 2013 to 2017 were analyzed. Age-standardized rates were calculated by the direct method, using the world standard population. Complementary, incidence (2002-2017) and mortality (1990-2017) trends were studied for the leading sites. Results: Among females, the most common cancers are breast, colon and rectum, lung, cervix and thyroid. The most frequent cancers in males are prostate, lung, colon and rectum, bladder and kidney. Lung, prostate and colorectal cancer are the leading causes of cancer death in males while breast cancer is the first cause of cancer death among females. Conclusions: Although cancer mortality has declined monotonously since 1990, cancer control is a challenge for Uruguay, wherein breast, lung and prostate cancer have very high incidence while the country must still make an effort to reduce other cancers that are very common in economically less favored countries.